PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PREDICTION GUIDE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 6 LUBUK BASUNG TAHUN PELAJARAN 2013/2014 - Silviana, Iga; Zulfaneti, Zulfaneti; Mardiyah, Ainil (Pendidikan Matematika, 2014)
Â ABSTRACTÂ This research was conducted based on the studentâs understanding on mathematics concept was still low and the low curiosity of student to the subject material. This research was aimed at revealing wheather the use of Prediction Guide technique could give a better effect on the studentâs understanding on mathematics concept than conventional learning in class VIII SMPN 6 Lubuk Basung. This was an experimental research which used random desain towardÂ  subject. The instrument of the research was test on mathematics concept. The data then was analyzed by using t-test assisted with MINITAB. Based on theÂ  data analysis, it was revealed that the sample was distributed normally and had homogeny variant. The result of hypothesis test showed that p-value (0,023) was smaller than indicating that the hypothesis was accepted. Hence, it was concluded that the application of Prediction Guide technique could improve the studentsâ understanding on mathematics concept better than that of the conventional learning.